"Mirror, mirror, am I as my coach sees me?": Discrepancy between athlete self-appraisals and reflected appraisals of their coach, and relations with athlete burnout - Trouilloud, D.; Isoard-Gautheur, S.; Roux, V. (Journal of Clinical Sport Psychology, 2023)
Using a person-centered approach, this study was conducted to identify (a) specific athlete profiles in terms of degree of discrepancy between their self-appraisals and the reflected appraisals of their coach and (b) the relations between these profiles and athlete burnout. Athletes (N = 369; Mage = 21.15 years) fulfilled measures of self-appraisals, reflected appraisals of their coach, and burnout. Latent profile analysis allowed the identification of three profiles: concordance (84%), positive discrepancy (11%), and negative discrepancy (5%). Analyses revealed relationships between athletes` profile membership and the three dimensions of burnout: emotional and physical exhaustion, sport devaluation, and reduced sense of accomplishment. More specifically, results indicated that athletes with a positive discrepancy profile (i.e., who rated themselves more positively than they think their coaches see them) were more at risk of burnout. This study contributes to existing research on psychosocial determinants of athlete burnout in the context of the coach-athlete relationship.